2021
DOI: 10.1021/jacs.1c10574
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Cross-Metathesis of Tetrafluoroethylene with a Seven-Membered N-Heterocyclic-Carbene–Ruthenium Catalyst

Abstract: A drastic increase in catalyst turnover number (TON) was accomplished in the cross-metathesis of tetrafluoroethylene (TFE) and vinyl ethers. Under a continuous flow of TFE, catalyst Ru7, which contains a seven-membered N-heterocyclic carbene (NHC) ligand, reached a TON of 4100; this is 2 orders of magnitude higher than the highest hitherto reported value. Mechanistic studies revealed that the expanded NHC successfully destabilizes the stable intermediates with a difluorocarbene structure, which strongly promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Moreover, G2-tol significantly outpaced G2, likely owing to the less sterically hindered NHC ligand of G2-tol facilitating the propagating cycloaddition reaction. The ruthenium catalyst bearing a seven-membered ring NHC, which exhibits high efficiency for the cross metathesis of tetrafluoroethylene and enol ethers, 36 gave almost the same result as HG2 (Scheme S10).…”
Section: ■ Results and Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Moreover, G2-tol significantly outpaced G2, likely owing to the less sterically hindered NHC ligand of G2-tol facilitating the propagating cycloaddition reaction. The ruthenium catalyst bearing a seven-membered ring NHC, which exhibits high efficiency for the cross metathesis of tetrafluoroethylene and enol ethers, 36 gave almost the same result as HG2 (Scheme S10).…”
Section: ■ Results and Discussionmentioning
confidence: 58%
“…Next, the second half of our hypothesis was interrogated, and ring-opening cross metathesis with an enol ether was carried out, enol ethers having been shown to be effective partners for cross metathesis with fluoroalkenes in ruthenium-catalyzed olefin metathesis (vide supra). , NBE1F and NBE2F were independently reacted with ethyl vinyl ether (3 equiv) in the presence of G2 (1 mol %) at room temperature (see the Supporting Information). The corresponding ring-opened adducts were cleanly formed without side products and isolated in good yields (75% from NBE1F , 69% from NBE2F ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Akiyama, Nozaki, and co-workers have reported a novel ruthenium catalyst that bears a seven-membered NHC ligand (49), which catalyzes the cross-metathesis reaction between TFE and vinyl ether 48 with a TON of 4100 (Scheme 23A). 57 The seven-membered NHC lowers the energy barrier via the destabilization of the difluoromethylidene species, which is supported by DFT calculations as well as by an analysis of the Xray structure of the difluoromethylidene complex. The authors also directed their efforts to the modification of the reaction conditions, which revealed that a reaction with flowing TFE gives a higher turnover than that in a sealed reactor.…”
Section: Ruthenium Olefin Metathesis Of Tfementioning
confidence: 68%
“…To change the reactivity of free difluorocarbene, its transition metal complexes are powerful alternatives as intermediates for the synthesis of fluorinated compounds. 47 The same silyl dienol ethers 21 underwent normal [4+1] cycloaddition with difluorocarbene under copper( i ) catalysis to afford the isomeric products 25 (β,β-difluorocyclopentanone-derived silyl enol ethers, Scheme 14, –CF 2 – introduction). 48 It seems likely that the copper difluorocarbene complex generated in situ from BrCF 2 CO 2 Na is sufficiently electrophilic to react with 21 , generating an alkylcopper species that is, in turn, nucleophilic and undergoes a 5- endo-trig cyclization like that shown in Scheme 11, leading to the corresponding products.…”
Section: Discussionmentioning
confidence: 99%